Spontaneous Intramural Duodenal Hematoma: Pancreatitis, Obstructive Jaundice, and Upper Intestinal Obstruction - Chalerm Eurboonyanun; Kulyada Somsap; Somchai Ruangwannasak; Anan Sripanaskul (Case Reports in Surgery)
Nontraumatic intramural duodenal hematoma can cause upper gastrointestinal tract obstruction, upper gastrointestinal hemorrhage, jaundice, and pancreatitis and may be present in patients with normal coagulation. However the pathogenesis of the condition and its relationship with acute pancreatitis remain unknown. We present a case of spontaneous intramural duodenal hematoma and a case of successful nonoperative treatments.